Fostering social inclusion in development-oriented digital food system interventions - Steinke, Jonathan; Schumann, Charlotte; Langan, Simon J.; Müller, Anna; Opola, Felix Ouko; Ortíz Crespo, Berta; Etten, Jacob van (Elsevier, 2024)
CONTEXT Digital innovations can enhance the participation of often-marginalized social groups – including women and resource-poor farmers in low- and middle-income countries – in sustainable, profitable food systems. But digital interventions can also reinforce existing inequities by further increasing the competitive advantage of user groups privileged with literacy, access to smartphones, or high investment capacity. To ensure that the digital transformation in the Global South leaves no one behind, therefore, deliberate efforts are needed to promote the inclusivity of emerging digital innovations. To date, however, there is a lack of practical guidelines and tools to critically assess, demonstrate, and enhance the inclusivity of digital food systems interventions. Too often, inclusivity remains a blurry concept and distant objective. In result, digital development researchers and practitioners have limited incentives for investing time and effort into safeguarding inclusivity.